2019
DOI: 10.3390/ijms20061380
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interaction among KCa and TRP Channels for Cardiovascular Physiology: Modern Perspectives on Aging and Chronic Disease

Abstract: Effective delivery of oxygen and essential nutrients to vital organs and tissues throughout the body requires adequate blood flow supplied through resistance vessels. The intimate relationship between intracellular calcium ([Ca2+]i) and regulation of membrane potential (Vm) is indispensable for maintaining blood flow regulation. In particular, Ca2+-activated K+ (KCa) channels were ascertained as transducers of elevated [Ca2+]i signals into hyperpolarization of Vm as a pathway for decreasing vascular resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 192 publications
(248 reference statements)
0
16
0
Order By: Relevance
“…Using arterial pressure myograph, other investigators have demonstrated SKA-31-evoked inhibition of myogenic tone in rat cremaster, middle cerebral arteries [19], and mesenteric arteries [20] in normotensive animals while hypertensive Cx40- or K Ca 3.1 -deficient mice were not affected by the eNOS inhibitor l -NAME. Differences in NO involvement in K Ca channel activator-mediated effects might result from experimental procedures and/or nature of the vasoconstrictor stimulus used [42,43]. Thus, it has been recently suggested, that a link between K Ca channel-mediated hyperpolarization and NO production in regulation of smooth muscle cell contractility exists [42,44].…”
Section: Discussionmentioning
confidence: 99%
“…Using arterial pressure myograph, other investigators have demonstrated SKA-31-evoked inhibition of myogenic tone in rat cremaster, middle cerebral arteries [19], and mesenteric arteries [20] in normotensive animals while hypertensive Cx40- or K Ca 3.1 -deficient mice were not affected by the eNOS inhibitor l -NAME. Differences in NO involvement in K Ca channel activator-mediated effects might result from experimental procedures and/or nature of the vasoconstrictor stimulus used [42,43]. Thus, it has been recently suggested, that a link between K Ca channel-mediated hyperpolarization and NO production in regulation of smooth muscle cell contractility exists [42,44].…”
Section: Discussionmentioning
confidence: 99%
“…Further work is necessary to study the changes these molecules undergo during aging. Recent evidence also supports the reverse role for BK Ca channels, in which they facilitate Ca 2+ influx into the cell interior through open nonselective cation (e.g., transient receptor potential; TRP) channels in accord with robust electrical (hyperpolarization) and concentration (~20,000-fold) transmembrane gradients for Ca 2+ [131]. Such an arrangement supports a feed-forward activation of membrane hyperpolarization while potentially affecting Ca 2+ spark-BK Ca channel coupling.…”
Section: Perspectivesmentioning
confidence: 76%
“…Accumulating evidence suggests that Ca 2+ -activated potassium channels may interact with Ca 2+ -permeable transient receptor potential channels to generate signal transduction between these channels in the vasculature 19. For example, TRPC1 is physically associated with BK Ca in vascular smooth muscle cells, and Ca 2+ entry via TRPC1 activates BK Ca to cause membrane hyperpolarization 20.…”
Section: Discussionmentioning
confidence: 99%